Career Support and Employee Performance Capacity in Nigeria - Okolie, Ugo Chuks; Memeh, Ndubuisi J.; Egbon, Thomastina Nkechi (Jurnal Administrasi Publik (Public Administration Journal), 2024)
In addition to being a crucial part of strategic human resource management, career support also serves as a tool for achieving organizational objectives. This study evaluates the impact of career support on workers' ability to perform. Most businesses in Nigeria are currently dealing with issues related to employee performance; this illustrates a significant challenge in the country's business environment. A qualitative research design was used for this study. To investigate the impact of career support on employees' performance, exploratory research based solely on findings from the analysis of the existing literature of various studies, periodicals, reports, and books relevant to the topic of study was employed. According to the findings of this study, career support is a crucial management tool that could be used in Nigeria to raise and improve employee performance. This implies that organizations in Nigeria may decline employee performance if career support issues are not taken seriously. The study concludes that an organization's career support initiatives directly impact how well its employees perform. The ability of employees to perform well is significantly positively correlated with career support. The study suggests, among other things, that organizations continue to treat career support very seriously to boost workers' productivity.